2010
DOI: 10.1128/ec.00378-09
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus fumigatus P-Type Golgi Apparatus Ca 2+ /Mn 2+ ATPase PmrA Is Involved in Cation Homeostasis and Cell Wall Integrity but Is Not Essential for Pathogenesis

Abstract: The Aspergillus fumigatus ⌬pmrA (Golgi apparatus Ca 2؉ /Mn 2؉ P-type ATPase) strain has osmotically suppressible basal growth defects and cationic tolerance associated with increased expression of calcineurin pathway genes. Despite increased ␤-glucan and chitin content, it is hypersensitive to cell wall inhibitors but remains virulent, suggesting a role for PmrA in cation homeostasis and cell wall integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…In C. albicans, chitin induces an inflammatory response by stimulating monocytes to synthesize IL-1␤ (42). Recently, it has been reported that a ⌬pmrA mutant of A. fumigatus has increased cell wall chitin content but normal virulence in the mouse model of invasive pulmonary aspergillosis (26). However, the virulence of this mutant was tested only in neutropenic mice.…”
Section: Discussionmentioning
confidence: 97%
“…In C. albicans, chitin induces an inflammatory response by stimulating monocytes to synthesize IL-1␤ (42). Recently, it has been reported that a ⌬pmrA mutant of A. fumigatus has increased cell wall chitin content but normal virulence in the mouse model of invasive pulmonary aspergillosis (26). However, the virulence of this mutant was tested only in neutropenic mice.…”
Section: Discussionmentioning
confidence: 97%
“…The impaired growth of the ΔhacA/ΔderA mutant could be partially rescued on medium containing sorbitol, an osmoprotectant that prevents swelling and lysis of strains that lack cell wall integrity. 26 However, this protection was incomplete, suggesting that defects in processes other than cell wall homeostasis also contribute to the abnormal growth of this mutant (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the deletion of A. fumigatus pmrA, encoding a golgi Ca 2+ /Mn 2+ P-type ATPase, showed a basal growth defect and cationic tolerance associated with increased expression of calcineurin pathway genes (Pinchai et al, 2010). The functions of three calcium transporters, pmcA , pmcB , and pmcC ( PMC1 homologs) were also investigated and cyclosporine A was able to modulate the sensitivity of these mutant strains to calcium and manganese salts, revealing their dependence on calcineurin (Dinamarco et al, 2012).…”
Section: Calcineurin In Ph Stress Temperature Stress Response Andmentioning
confidence: 99%